Hubungan Perhatian Orang Tua dengan Motivasi dan Kesiapan Belajar Siswa Kelas V SDN 2 Surabaya Kec. Limbangan Kab. Garut - Abdul Hakim; Indriyanti Karmila (Institut Pendidikan Indonesia, 2022)
This study uses the correlational method to determine the relationship between parental attention and learning motivation and learning readiness of fifth grade students at SDN 2 Surabaya. Based on the results of the study showed that: (1) there is a relationship between parental attention and student learning motivation with a significance value for the effect of parental attention on motivation is 0.013 < 0.05 and for the tcount value is 2.681 > 2.055, (2) there is a relationship between people's attention parents with student learning readiness, this is evidenced by the significance value for the effect of parental attention on learning readiness is 0.000 < 0.05 and for the t count value is 4.684 > 2.055, (3) parental attention has an influence on learning motivation and student readiness to learn by see a percentage of 22.3% parental attention has an influence on student motivation. Meanwhile, 46.78% of parents' attention has an influence on the learning readiness of fifth grade students at SDN 2 Surabaya.